Lack of Association between NYD-SP18 Variant and Obesity. The Health Alcohol and Psychosocial Factors in Eastern Europe Study - Hubacek, Jaroslav A; Pikhart, Hynek; Kubinova, Ruzena; Peasey, Anne; Malyutina, Sofia; Pajak, Andrzej; Tamosiunas, Abdonas; Bobak, Martin (Annals of nutrition & metabolism, 2016)
AIM: To replicate the finding that the polymorphism rs6971091 within the NYD-SP18 gene is associated with body mass index (BMI). METHOD: We analysed data of 29,284 adults (46.2% of males, mean age 58.9 (SD 7.3), mean BMI 28.6 (5.0 kg/m2)) examined within the Health Alcohol and Psychosocial Factors in Eastern Europe study in the Czech Republic, Poland, Lithuania and Russia. RESULTS: BMI did not differ by rs6971091 genotype. In men, the mean BMI (SEs) in GG, GA and AA carriers were 27.8 (0.05), 27.9 (0.06) and 27.9 (0.14) kg/m2, respectively, (p = 0.26); in women, the corresponding values were 29.2 (0.06), 29.1 (0.07) and 29.1 (0.16), p = 0.57. In Czech subjects (n = 6,752), for whom the FTO rs17817449 genotype was available, there was no interaction between the NYD-SP18 and FTO polymorphisms in determination of BMI. Adjustment for age, energy and fat intake and physical activity did not materially change the results. There was no association of the NYD-SP18 genotype with waist-hip ratio. CONCLUSION: This study in a large Slavonic population sample suggests that the rs6971091 variant within the NYD-SP18 gene is not an important determinant of obesity in middle-aged persons.
Keywords: senioři; index tělesné hmotnosti; alely; Genetic Predisposition to Disease; Poland; jaderné proteiny; Reproducibility of Results; Russia; Waist-Hip Ratio; jednonukleotidový polymorfismus; Alleles; Obesity; reprodukovatelnost výsledků; Nuclear Proteins; Česká republika; Cohort Studies; Rusko; Middle Aged; registrace; mužské pohlaví; Overweight; Czech Republic; Polsko; Registries; kohortové studie; Body Mass Index; gen pro FTO; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; genetické asociační studie; Humans; Lithuania; lidé středního věku; frekvence genu; obezita; nadváha; Gene Frequency; Genetic Association Studies; genetická predispozice k nemoci; Aged; poměr pasu a boků; Litva; lidé; Male; Polymorphism, Single Nucleotide